2008 3rd Petascale Data Storage Workshop 2008
DOI: 10.1109/pdsw.2008.4811886
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performance of solid state devices and mechanical disks

Abstract: Abstract-In terms of performance, solid state devices promise to be superior technology to mechanical disks. This study investigates performance of several up-to-date high-end consumer and enterprise Flash solid state devices (SSDs) and relates their performance to that of mechanical disks. For the purpose of this evaluation, the IOZone benchmark is run in single-threaded mode with varying request size and access pattern on an ext3 filesystem mounted on these devices. The price of the measured devices is then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 3 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…A main approach in that direction is the use of Solid State Drives (SSD's) which have been shown to improve performance on typical database operations such as sorting and therefore energy efficiency [4]. Obviously SSDs are faster in such kind of scenarios [10], but there are other tradeoffs as a replacement for HDDs with most obvious the cost per gigabyte (Schall et. all [11], Schröder-Preikschat et.…”
Section: Background and Motivationmentioning
confidence: 99%
“…A main approach in that direction is the use of Solid State Drives (SSD's) which have been shown to improve performance on typical database operations such as sorting and therefore energy efficiency [4]. Obviously SSDs are faster in such kind of scenarios [10], but there are other tradeoffs as a replacement for HDDs with most obvious the cost per gigabyte (Schall et. all [11], Schröder-Preikschat et.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Storage already represents more than a third of a typical datacenter's direct power consumption [27], as shown in Figure 1, and can be over 70% for storage-heavy installations [33]. The left three drives (highlighted) are solid-state disks (SSDs) [Performance data from Polte et al [24], with average power estimated from datasheets and online reviews. ]…”
Section: The Enterprise Storage Power Challengementioning
confidence: 99%
“…Polte et al have shown that enterprise-level Flashbased SSDs can provide more than two orders-ofmagnitude improvement in performance over hard disks for random access patterns [24]. We have incorporated published power data on six of the storage devices they tested to estimate the power efficiency (in thousands of I/O operations per second (IOPS) per Watt) as shown in Figure 2.…”
Section: The In-place Update Problemmentioning
confidence: 99%
“…As expected, the SSDs are orders of magnitude faster than the traditional disk drives. To better understand the behavior of flash memory based SSDs, Polte et al [2008] performed a thorough investigation about the performance of several high-end consumer and enterprise SSDs, and compared their performance to a few generally available disk drives. They reported that for sequential access pattern, the SSDs are up to 10 times faster for reads and up to 5 times faster for writes than the magnetic disk drives.…”
mentioning
confidence: 99%
“…), which can be integrated into the controller of SSDs, have significant impacts on the performance of SSDs. The reader is referred to [Polte et al 2008] for details. Power consumption depends on the characteristics of different storage devices and data access patterns.…”
mentioning
confidence: 99%